Opening the black box: An observational study of teaching and learning interactions for paediatrics trainees on consultant ward rounds. (22nd May 2018) - Gray, Amy; Enright, Helen
Abstract : Aim: Ward rounds are complex activities in which education must be balanced against service. Limited evidence exists regarding how to optimise ward round education. In order to improve the educational experience, we aimed to understand the teaching and learning interactions on ward rounds with a particular focus on the experience of paediatric trainees. Methods: We conducted an initial quantitative survey as a needs assessment regarding learning and teaching in clinical settings using a structured survey of 21 trainees. This was followed by an observational study using focused ethnography of 20 consultant ward rounds in a general medical department of tertiary paediatric hospital. We used a structured observation form to document ward round characteristics and educational interactions. Data were analysed using inductive content analysis to understand key influences on teaching and learning interactions. Results: Trainees reported a discrepancy between the actual educational value of ward rounds (mean rating 2.7/5) and what they desired (mean 4.3/5). Ward round ethnography revealed examples of excellent education and practice alongside missed opportunities. Explicit education on rounds was dominated by technical content with little focus on other aspects of professionalism. Major influences on educational interactions were the ward round model – consultant‐as‐expert versus learner‐centred – and the hidden curriculum. Conclusion: There are many examples of excellence in ward round education, yet there remains substantial scope to better harness the education potential of rounds. This requires us to challenge assumptions, enable feedback and reflection and make learning explicit – while putting the learner at the centre of educational opportunities.